To find the equivalent expression using modeling, make a table with the terms of 2x+y−3z2x+y−3z along the top and 5 on the left. Then multiply each term of 2x+y−3z2x+y−3z with 5.

2x y −3z

5 10x 5y −15z

The equivalent expression is the sum of the products so the equivalent expression is 10x+5y−15z.

The Distributive Property states that a(b+c)=ab+aca(b+c)=ab+ac. Using the Distributive Property gives:

=5(2x)+5(y)+5(−3z) Distributive Property.

=10x+5y−15z Multiply.

2x y −3z

5 10x 5y −15z

The equivalent expression is the sum of the products so the equivalent expression is 10x+5y−15z.

The Distributive Property states that a(b+c)=ab+aca(b+c)=ab+ac. Using the Distributive Property gives:

=5(2x)+5(y)+5(−3z) Distributive Property.

=10x+5y−15z Multiply.